# Solve the linear equation: m - (m - 1)/2 = 1 - (m - 2)/3

**Solution:**

m - (m - 1)/2 = 1 - (m - 2)/3

Multiply both sides by the LCM of the denominators to get rid of fractional denominator.

Now transpose variables to one side and constants to another side to form a linear equation.

m - (m - 1)/2 = 1 - (m - 2)/3

LCM of the denominators is 6

Multiply the LCM on both sides

⇒ 6[m - (m - 1)/2] = 6[1 - (m - 2)/3]

⇒ 6m - 3m + 3 = 6 - 2m + 4

⇒ 5m = 7

Hence,

m = 7/5

**Video Solution:**

## Solve the linear equation: m - (m - 1)/2 = 1 - (m - 2)/3

### NCERT Solutions Class 8 Maths - Chapter 2 Exercise 2.5 Question 6

**Summary:**

The solution to the given linear equation m - (m - 1)/2 = 1 - (m - 2)/3 is m = 7/5